2013
DOI: 10.1259/dmfr/80179163
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of apical periodontitis detected in cone beam CT images of a Brazilian subpopulation

Abstract: Objectives: The aim of this study was to determine the prevalence of apical periodontitis (AP) detected in cone beam CT (CBCT) images from a database. Methods: CBCT images of 300 Brazilian patients were assessed. AP images were measured in three dimensions. Age, gender, number and location of total teeth in each patient were considered. AP location was considered according to tooth groups. The extent of AP was determined by the largest diameter in any of the three dimensions. Percentages and the x 2 test were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 27 publications
9
39
1
2
Order By: Relevance
“…This difference may be explained by the fact that women take more care of their health and appearance than men8, which may lead them to seek dental care immediately in symptomatic cases, while men choose to postpone treatment 20 . On the other hand, men and women presented a similar prevalence of periradicular diseases (p=0.953), confirming what has been previously reported in other studies 11,19,21 . The results presented here indicated that the prevalence of pulp diseases was higher in people under 50 years of age, whereas periradicular diseases affected more patients over 50 years of age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This difference may be explained by the fact that women take more care of their health and appearance than men8, which may lead them to seek dental care immediately in symptomatic cases, while men choose to postpone treatment 20 . On the other hand, men and women presented a similar prevalence of periradicular diseases (p=0.953), confirming what has been previously reported in other studies 11,19,21 . The results presented here indicated that the prevalence of pulp diseases was higher in people under 50 years of age, whereas periradicular diseases affected more patients over 50 years of age.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of chronic apical periodontitis in Brazilian subpopulations was target of previous studies 11,19 , which found a prevalence of chronic apical periodontitis of 3.4% 11 and 5.9% 19 , respectively, whereas in our study, which evaluated a larger population sample than those studies, we detected a higher prevalence, i.e., 34.81%.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Recently a periapical index based on cone beam-computed tomography (CBCTPAI) for identification of apical periodontitis has been proposed. The CBCT PAI is a 6-point (0-5) scoring system calculated from determining the largest lesional measurement in either the buccopalatal, mesio-distal, or axial dimension or taking into account expansion and destruction of cortical bone [8][9][10][11][12][13][14] (Table 2).…”
Section: Detection Of Apical Periodontitismentioning
confidence: 99%
“…However, there have been very few publications reporting on the prevalence 18 and characteristics of AP identified in CBCT exams.…”
Section: Introductionmentioning
confidence: 99%